2019
DOI: 10.3390/nano9111508
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Heavy Metal Removal from Wastewater Using an External Magnetic Inductor

Abstract: Magnetite nanoparticles (Fe3O4) of 12 ± 4 nm diameter are electrochemically synthesized for the adsorption and magnetic harvesting of Cr(VI) from contaminated simulated solutions. The removal of Cr(VI) from aqueous media follows pseudo-second-order kinetics. The adsorption efficiency is evaluated in three different scenarios. In standard conditions, i.e., at room temperature; in a thermal bath working at 60 °C, where the temperature could be considered homogeneous within the solution; and finally, under magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…273 Besides conversion, controllable magnetic heating can be applied to improve reaction selectivity, as demonstrated in hydrodeoxygenation reactions and cleavage of lignocellulose-derived products by Ni/FeNi 3 NPs (Figure 39C), 274 which achieves full conversion and 100% selectivity for 2-methylfuran from furfural and 2,5-dimethylfuran from 5-hydroxymethylfurfural. Magnetic heating has also been applied to remove Cr(VI) 275 and to degrade methyl blue dye. 276 These examples highlight the important aspects of magnetic heating: it can make the catalytic process potentially not only safer and cleaner but also more efficient and controllable.…”
Section: Magnetic Nanoparticles In Catalysismentioning
confidence: 99%
“…273 Besides conversion, controllable magnetic heating can be applied to improve reaction selectivity, as demonstrated in hydrodeoxygenation reactions and cleavage of lignocellulose-derived products by Ni/FeNi 3 NPs (Figure 39C), 274 which achieves full conversion and 100% selectivity for 2-methylfuran from furfural and 2,5-dimethylfuran from 5-hydroxymethylfurfural. Magnetic heating has also been applied to remove Cr(VI) 275 and to degrade methyl blue dye. 276 These examples highlight the important aspects of magnetic heating: it can make the catalytic process potentially not only safer and cleaner but also more efficient and controllable.…”
Section: Magnetic Nanoparticles In Catalysismentioning
confidence: 99%
“…They measured an adsorption capacity of up to 12.4 mg/g. The regeneration cycles of the magnetic nanomaterials showed a slight decrease (about 4%) in the removal efficiency, concluding that the nanomaterial can be reused for up to 4 cycles continuously [134]. Tao et al, showed an effective removal of heavy metal ions (Hg 2+ and Pb 2+ ) using thiol-functionalized magnetic mesoporous microspheres [135].…”
Section: Reusability Of Magnetic Nanoparticlesmentioning
confidence: 99%
“…Apart of the fact that IONPs can be efficiently recovered with an external magnetic field, facilitating its regeneration and reuse, environmental processes like the presented in previous sections can also be enhanced by taking advantage of the magnetic heating power of IONPs in the presence of AMF. In the case of adsorption with IONPs, Rivera et al presented the improvement of the adsorption capacity of chromium under an AMF [95]. Here, they showed much higher adsorption yields for IONP systems heated up with AMF than with common thermal heating even though both systems were set at the same global temperature.…”
Section: Boosting Environmental Processesmentioning
confidence: 99%